Tata Kelola Pemerintahan Terkait Alternatif SDM Pertahanan Dalam Rangka Efisiensi Anggaran Pertahanan - Endro Tri Susdarwono (Journal of Government and Politics (JGOP), 2020)
The purpose of this study is to describe governance related to alternative defense human resources in the context of defense budget efficiency embodied in the human resources of the reserve components and defense support components. This research is a qualitative research. This type of research uses a comprehensive analytic study and an analytical normative approach. The discussion regarding defense human resources needed to build a defense force includes active military, compulsory or conscripted military, voluntary military or reserve components and supporting components. Active military and mandatory military in relation to service are almost the same, it's just that the mandatory military has a limited period of service in accordance with the rules of the state. In taking into account the human resources of defense, it is not only active military and conscription, but includes reserve and supporting components. Human resource management is essentially a cycle from recruitment to separation - then the actual defense HR management must be carried out continuously. So thus, the management of human resources for defense of existing human resources (TNI personnel) must be carried out continuously, starting from recruitment, education, use, welfare, and separation. The TNI is a major component in the national defense system supported by the Komcad and Komduk. Two mandates of the national defense law that have not yet been resolved are the Komcad Draft Law and the Komduk Draft Law. And based on the description of human resource management, it is very important that this draft law be completed.